German „Technologie- und Gründerzentren” and the regional knowledge base: An empirical analysis of companies in Lower Saxony - Liefner, Ingo (Raumforschung und Raumordnung | Spatial Research and Planning, 2004)
Science parks (Technologie und Gründerzentren) aim at supporting newly founded high-tech companies. Thus, they are meant to contribute to technology transfer from universities and other public research institutes to companies. Theoretical considerations suggest that the amount of knowledge embodied within local universities and companies is a key determinant for technology transfer. This article analyzes whether differences in the regional knowledge potential are reflected in the technological level of firms supported by sience parks. This hypothesis can be confirmed: Firms in regions with high local knowledge potential show significantly higher technological levels regardless of their age, field, and size.